PERBANDINGAN PENGARUH PEMBERIAN ANALGETIK ETORICOXIB DENGAN NATRIUM DICLOFENAK TERHADAP RASA NYERI PASCA ODONTEKTOMI (IMPAKSI KELAS 1, MOLAR 3 RAHANG BAWAH) - Taufiqurrachman Taufiqurrachman; Kuswartono Mulyo (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background : Pain is a common complaint and frightening experience for patients post odontektomi so in need of process right and good. Diclofenak natrium analgesic drugs can not always be achieved the maximum in comparison with the type of drug that reaches the maximum etoricoxib appropriately and well.Objective : To determine the meaning of analgesic effect of etoricoxib with diclofenac natrium for pain odontektomi.Methods : This study is a quasi-experimental research design "post test only randomized controlled group design" with the double-blind technique. Samples in the two groups where each group numbered 16, namely the treatment group receive analgesic drugs etoricoxib 90 mg and control groups receive analgesic drugs diclofenak natrium 120 mg . Pain measured by VDS. Statistical test using unpaired tResults : The average score on the fifth day VDS results etoricoxib treatment group median 1 in the control group natrium diclofenak median 4 p = <0.001 for p <0.05, then conclude meaningful or significant differences. Gender, age, education, and experience no effect on the extraction of VDS score or not a confounding variables (p> 0.05).Conclusions : There are significant differences or significant postoperative pain between odontektomi VDS scores on etoricoxib 90 mg treatment group and control group diclofenak natrium 120 mg. Gender, age, education, and experience no effect on the extraction of VDS scores.